Pegbelfermin (BMS-986036): an investigational PEGylated fibroblast growth factor 21 analogue for the treatment of nonalcoholic steatohepatitis. (1st February 2020) - Verzijl, Cristy R.C.; Van De Peppel, Ivo P.; Struik, Dicky; Jonker, Johan W.
ABSTRACT: Introduction : Nonalcoholic fatty liver disease (NAFLD) is the most common liver disease worldwide and is strongly associated with obesity and insulin resistance. NAFLD refers to a spectrum of disorders ranging from asymptomatic hepatic steatosis (nonalcoholic fatty liver, NAFL) to nonalcoholic steatohepatitis (NASH), which increases the risk of developing more severe forms of liver disease such as progressive fibrosis, cirrhosis, and liver cancer. Currently, there are no food and drug administration (FDA) approved drugs to treat NASH. Pegbelfermin (BMS-986036) is a PEGylated fibroblast growth factor 21 (FGF21) analogue that is under investigation for the treatment of NASH. Areas covered : We reviewed the (pre)clinical pegbelfermin studies and compared these with other studies that assessed FGF21 and FGF21 analogues in the treatment of NASH. Expert opinion : With no FDA approved treatments available for NASH, there is an urgent need for novel therapies. Pegbelfermin is a systemic treatment with pleiotropic effects on various tissues. Short-term adverse effects are limited, but more research is required to study potential long-term safety issues. In a phase 2a trial, pegbelfermin has shown promising improvements in several NASH related outcomes. However, clinical trials demonstrating long-term benefits on hard outcomes such as liver histology, cirrhosis development, or survival are required for further validation.